Seroepidemiology Survey of Bovine Alphaherpesvirus 1 (BoHV-1) in Unvaccinated Beef Bubalines (Bubalus bubalis) from Southern Brazil - Oliveira, Rodrigo Azambuja Machado de; Fritzen, Juliana Torres Tomazi; Alfieri, Amauri Alcindo; Lisbôa, Júlio Augusto Naylor; Ollhoff, Rudiger Daniel; Filho, Ivan Roque de Barros (Acta Scientiae Veterinariae, 2021)
Background: The bovine alphaherpesvirus type 1 (BoHV-1) belonging to the order Herpesvirales, family Herpesviridae, subfamily Alphaherpesvirinae and genus Varicellovirus.Bovine alphaherpesvirus 1 (BoHV-1) infections have a great importance due to the high rates of dissemination in cattles worldwide. Although, the BoHV-1 was largely related in cattle, buffaloes were also classified as host for the virus. However, studies that determine seroepidemiological data in this species are scarce and necessary. The aim of the present study was to determine the presence of antibodies against BoHV-1 in healthy beef buffaloes using the virus neutralization (VN) technique. Cases: This work portrays an epidemiological survey, based on a sectional study characterized by blood samples collected from 54 Murrah buffalo, aged 6 to 24 months, from the municipalities of Guaraqueçaba, Ponta Grossa, Antonina and Doutor Ulysses, located in Paraná state, being 20, 14, 10 and 10 samples from each location, respectively. Thirty-seven percent (20/54) of the samples were collected at slaughterhouse with registration at the Federal Inspection Service (SIF) of the Ministry of Agriculture, Livestock and Food Supply (MAPA), and 63% (34/54) at the buffalo’s farms. The serum samples were collected in sterile tubes without anticoagulant in stored isothermal boxes, with serum separation and stored at -20ºC. The samples were sent to the Animal Virology Laboratory of Universidade Estadual de Londrina, UEL for serological analysis. Serological diagnosis using the virus neutralization (VN) technique was performed according the OIE manual of diagnostic tests and vaccines for terrestrial animals, using the BoHV-1 Los Angeles strain. Forth-five of the 54 samples (83.3%) evaluated generated titers of antibodies against BoHV-1 present in all evaluated herds, and the samples collected in herd from Antonina city were 100% positive, following by 80% in Guaraqueçaba and Doutor Ulysses city, and 78.6% in Ponta Grossa city. In relationship to the titration of anti-bovine herpesvirus 1 antibodies (BoHV-1), it was found that 23/45 (51.12%) of the samples had titers ≤ 16, 13/45 (28.88 %) with indexes between 32-64, and 9/45 (20%) with levels above 128. Discussion: The confirmation of the presence of antibodies against BoHV-1 in the buffalo samples tested in the present study proves the circulation of the agent in the studied species, with a homogeneous distribution of bovine alphaherpesvirus 1 in all the evaluated herds. There was high variability in antibody titers against BoHV-1 from all herds, and the occurrence of a high number of buffaloes reactive to BoHV-1 and with high antibody titers suggests a course of active or reactive infections in these animals. In only one of the herds, the age of the animals studied varied between 6 to 8 months. The fact that these animals are lactating raises the possibility of anti-BoHV-1 antibodies being acquired by breastfeeding. The results obtained allow to conclude, considering the fact that the animals are not vaccinated against BoHV-1, the presence of circulating antibodies is from a natural infection, and the positivity in all farms tested denotes the endemicity of the BoHV-1 infection in herds. To the best knowledge of the authors, this is the first study on the detection and measurement of antibodies against BoHV-1 in healthy and unvaccinated buffaloes in the state of Paraná, southern Brazil, showing a high frequency of seroreagent animals.